FLUORIDE RELEASE FROM GLASS IONOMER CEMENT CONTAINING FLUOROAPATITE AND HYDROXYAPATITE - Malik, Sofia; Ahmed, Muhammad Adeel; Choudhry, Ziaullah; Mughal, Nouman; Amin, Muhammad; Lone, Muneeb Ahmed (Journal of Ayub Medical College Abbottabad, 2018)
Background: Many investigators reported the amount of fluoride release from glass ionomer cement. However, the work on fluoride release from GIC containing fluoroapatite and hydroxyapatite is scarce. Therefore, this study was conducted to find out the amount of fluoride release from Glass ionomer cement containing fluoroapatite and hydroxyapatite. Methods: The study was conducted in the Department of Materials, Queen Marry University of London. A total of 108 samples equally divided in to three groups namely fluoroapatite added GIC, Hydroxyapatite added GIC as an experimental group and unmodified GIC as a control group. The specimens were prepared by mixing powder and liquid in the ratio of 1:1. Amount of fluoride released was measured by Ion electrode method at 1, 3, 7, 14, 21 and 28 days. Results: On day 1, the combination of FA +GIC showed the highest amount of fluoride release followed by the control group (GIC) whereas the combination of HA+GIC released the least amount of fluoride. On day 7, the amount of fluoride release started declining in all three groups. The amount of fluoride release continued decreasing on day 21 in which combination of FA +GIC and the control group are shown to release equal amount of fluoride whereas the combination of HA+GIC gave the least activity the amount of fluoride release fall to a minimum level in all three group by day 28. Conclusion: It is concluded that addition of fluoroapatite into GIC has significant effect on the amount of fluoride release as compared to GIC alone; however, addition of hydroxyapatite into GIC has no additive effect on the amount of fluoride release. Keyword: Fluoroapatite, Hydroxyapatite, Glass ionomer cement